2020
DOI: 10.1534/genetics.120.303442
|View full text |Cite
|
Sign up to set email alerts
|

Normal Patterns of Histone H3K27 Methylation Require the Histone Variant H2A.Z inNeurospora crassa

Abstract: Neurospora crassa contains a minimal Polycomb repression system, which provides rich opportunities to explore Polycomb-mediated repression across eukaryotes and enables genetic studies that can be difficult in plant and animal systems. Polycomb Repressive Complex 2 is a multi-subunit complex that deposits mono-, di-, and tri-methyl groups on lysine 27 of histone H3, and tri-methyl H3K27 is a molecular marker of transcriptionally repressed facultative heterochromatin. In mouse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 104 publications
1
15
0
2
Order By: Relevance
“…graminearum ’s genome, including genes involved in secondary metabolism [ 51 ]. However, regarding the function of H2A.Z in fungi, very few studies were carried out in Neurospora crassa studying specifically the function of H2A.Z and identifying a role in oxidative stress response [ 52 , 53 ] as well as a link with the deposition of H3K27me3 [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…graminearum ’s genome, including genes involved in secondary metabolism [ 51 ]. However, regarding the function of H2A.Z in fungi, very few studies were carried out in Neurospora crassa studying specifically the function of H2A.Z and identifying a role in oxidative stress response [ 52 , 53 ] as well as a link with the deposition of H3K27me3 [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…H2A.Z is reported to promote chromatin accessibility in in embryonic stem cells [ 60 ]⁠⁠. We compared previously published H2A.Z ChIP-seq data [ 22 ] to our ATAC-seq data and found that H2A.Z was enriched flanking most, but not all ACRs (e.g. see Cluster 3).…”
Section: Resultsmentioning
confidence: 83%
“…To quantify the level of accessibility in heterochromatin and euchromatin, we used bedtools intersect to determine the number of ACRs that overlap with H3K27me2/3 or H3K9me3 (Table S3 ). H3K27me2/3 is enriched in 309 domains covering 6% of the genome [ 22 ]⁠. We identified 68/7132 ACRs that overlap with called H3K27me2/3 enriched regions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations